Peningkatan Kualitas Lingkungan Mushola at Taqwa Rawa Mekar Jaya Tangerang Selatan Melalui Peremajaan Instalasi Listrik dan Penerangan yang Optimal - Jan Setiawan; Heranudin Heranudin; Heri Kusnadi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
As part of performing the Tri Dharma of Higher Education, community service activities were carried out to implement the rejuvenation of electrical installations, additional lights, and fans in Mushola At-Taqwa Rawa Mekar Jaya, South Tangerang with collaboration between the service team and members of DkM Mushola At-Taqwa in order to improve the quality of the mushola environment. These improvement expected to support the implementation of conducive and comfortable praying. The scope of the service carried out includes rejuvenating electrical installations by replacing and fixing electrical installations. Optimizing lighting both in the main room and on the mushola terrace using LED lights so as to give an aesthetic impression and obtain energy efficiency. Adding an electric fan to increase comfort for the congregation during hot weather conditions and remain energy efficient. In addition, a socialization on safe electrical practices was conducted, increasing the awareness of DkM members and the congregation of Mushola At-Taqwa on the correct and good electrical installation standards and their potential hazards. This study contributes to broadening the understanding of the technical and social implementation of community service activities carried out by Pamulang University in the community.